Lenition, perception and neutralisation*. Issue 1 (15th June 2016) - Katz, Jonah
Abstract : This paper argues that processes traditionally classified as lenition fall into at least two subsets, with distinct phonetic reflexes, formal properties and characteristic contexts. One type, referred to as loss lenition, frequently neutralises contrasts in positions where they are perceptually indistinct. The second type, referred to as continuity lenition, can target segments in perceptually robust positions, increases the intensity and/or decreases the duration of those segments, and very rarely results in positional neutralisation of contrasts. While loss lenition behaves much like other phonological processes, analysing continuity lenition is difficult or impossible in standard phonological approaches. The paper develops a phonetically based optimality-theoretic account that explains the typology of the two types of lenition. The crucial proposal is that, unlike loss lenition, continuity lenition is driven by constraints that reference multiple prosodic positions.